2017
DOI: 10.1016/j.biortech.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of cashew apple bagasse using protic ionic liquids: Enhanced enzymatic hydrolysis

Abstract: To enhance the enzymatic digestibility of cashew apple bagasse (CAB) feedstock in order to produce sugar fermentation-derived bioproducts, the CAB was subjected to three different pretreatments with the ionic liquid 2-hydroxyl-ethylammonium acetate (2-HEAA) and characterized by FTIR, NMR and chemical methods. All conditions were able to delignify CAB, however the best lignin removal (95.8%) was achieved through the method performed with 8.7% w/w of CAB/2-HEAA ratio at 130°C for 24h. Although the cellulose crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(24 citation statements)
references
References 42 publications
1
18
0
2
Order By: Relevance
“…Further, the amino acid APIL used is thermally unstable and likely to be expensive to synthesize, limiting its commercial applications [ 40 ]. These drawbacks have motivated research into the development of moisture-tolerant, easily synthesized and inexpensive protic ionic liquids (PILs) with comparable performance [ 41 43 ]. Recently, Rocha et al [ 44 ] achieved 68% glucose yields following pretreatment of sugarcane bagasse at 10 wt% loading using PIL [H 3 N(CH 2 ) 2 OH][OAc]:[H 2 O] (5:1 w/w) at 150 °C for 3.5 h, though a severe (~ 33%) reduction in hydrolysis yields was observed after five successive recycles of the PIL.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the amino acid APIL used is thermally unstable and likely to be expensive to synthesize, limiting its commercial applications [ 40 ]. These drawbacks have motivated research into the development of moisture-tolerant, easily synthesized and inexpensive protic ionic liquids (PILs) with comparable performance [ 41 43 ]. Recently, Rocha et al [ 44 ] achieved 68% glucose yields following pretreatment of sugarcane bagasse at 10 wt% loading using PIL [H 3 N(CH 2 ) 2 OH][OAc]:[H 2 O] (5:1 w/w) at 150 °C for 3.5 h, though a severe (~ 33%) reduction in hydrolysis yields was observed after five successive recycles of the PIL.…”
Section: Introductionmentioning
confidence: 99%
“…The use of protic ionic liquids (PILs) for lignin extraction is an emergent area of research that has been demonstrated to have relatively high lignin extraction efficiency [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. PILs are a unique class of ionic liquids (also known as liquid salts) that are produced via a simple acid–base neutralization, such as the combination of organic acids and amine bases [ 21 ], and thus, are relatively cost competitive chemicals [ 21 ] (note: one or more of the ions can also be inorganic).…”
Section: Introductionmentioning
confidence: 99%
“…However, the RS pretreated with AHP‐ILW retained the highly crystalline cellulose structure, indicating that the removal of amorphous constituents still dominated. The same results were also reported in previous studies on IL pretreatment . These results implied that the AHP‐ILW pretreatment could selectively dissolve most of the lignin to facilitate enzymolysis and fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…The same results were also reported in previous studies on IL pretreatment. 33,34 These results implied that the AHP-ILW pretreatment could selectively dissolve most of the lignin to facilitate enzymolysis and fermentation. Besides, the CLSM images could show the fluorescence images of the lignin distribution.…”
Section: Sscf Of the Combined Pretreated Rsmentioning
confidence: 89%